2015
DOI: 10.1371/journal.pone.0124812
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis Induced by Ginkgo biloba (EGb761) in Melanoma Cells Is Mcl-1-Dependent

Abstract: Melanoma is an aggressive skin cancer. Unfortunately, there is currently no chemotherapeutic agent available to significantly prolong the survival of the most patients with metastatic melanomas. Here we report that the Ginkgo biloba extract (EGb761), one of the most widely sold herbal supplements in the world, potently induces apoptosis in human melanoma cells by disturbing the balance between pro- and anti-apoptosis Bcl-2 family proteins. Treatment with EGb761 induced varying degrees of apoptosis in melanoma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 45 publications
4
16
0
Order By: Relevance
“…In the present study, we initially found that EGb761 showed no toxic effect on PIG1 cells (data not shown), which was consistent with previous studies . The patients with vitiligo have inferior capacity against oxidative stress due to the lower activity of SOD and GSH‐Px .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In the present study, we initially found that EGb761 showed no toxic effect on PIG1 cells (data not shown), which was consistent with previous studies . The patients with vitiligo have inferior capacity against oxidative stress due to the lower activity of SOD and GSH‐Px .…”
Section: Discussionsupporting
confidence: 92%
“…One study reported that EGb761 could protect melanocytes against oxidative stress by activating antioxidase and inhibiting endoplasmic reticulum stress . However, some other studies have controversial findings that Ginkgo biloba or its principal components could induce the apoptosis of melanoma cells . Notably, several clinical trials have illustrated that the application of Ginkgo biloba extract can prevent the onset and the progression of vitiligo, indicating its therapeutic potential in treating vitiligo .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We showed that NiO‐NPs injection decreased the ATP level in isolated melanoma mitochondria. Various investigations have shown that apoptosis signaling is suppressed in melanoma, and this is one of the failure factors in the treatment of tumor …”
Section: Discussionmentioning
confidence: 99%
“…The research of Ginkgolides and Ginkgo flavonoids focus on three aspects: the protective neurons from apoptosis under different conditions [30] [31] [32] , inducing tumor cells apoptosis to exert protective effect [33] [34] [35] , inhibiting apoptosis of cardiomyocytes and endothelial cells (ECs) under hypoxia then exerts a potent protective effect [36] [37] . This paper demonstrated that Ginkgolides and Ginkgo flavonoids might protect hippocampal neurons from apoptosis and explore the possible mechanism.…”
Section: Discussionmentioning
confidence: 99%